13 Mycorrhizal fungi in Brazilian tropical biomes - de Moura, Jadson Belem; Vieira, Wagner Gonçalves [UNESP]; Filho, Luiz Cesar Lopes; de Souza, Rodrigo Fernandes; dos Santos Lucas, Leidiane; Ramos, Maria Lucrécia Gerosa (Elsevier, 2025)
Tropical Brazilian biomes, including the Amazon, Atlantic Forest, Cerrado, Pantanal, Caatinga, Tropical Dry Forest, and Chaco, are home to a vast diversity of mycorrhizal fungi that form crucial symbiotic associations with plants. These fungi facilitate the absorption of nutrients and water, hence improving plant health and productivity, especially in nutrient-poor soils. Arbuscular mycorrhizae predominate in most of these biomes, while ectotrophic mycorrhizae are less common but equally important in certain habitats. Environmental changes, such as deforestation and urbanization, negatively impact the diversity of mycorrhizal fungi, compromising the health of ecosystems. The preservation of mycorrhizal interactions is essential for the resilience and sustainability of tropical biomes, as they play a vital role in maintaining biodiversity, nutrient cycling, and soil structure. Sustainable management practices are crucial for protecting these fungi and ensuring the continuity of ecosystem services provided by tropical biomes.